Beribadah di Tengah Wabak Covid-19: Analisis Terhadap Fatwa Majelis Ulama Indonesia No 14 Tahun 2020 Berasaskan Teori Maqāṣid al-Sharī‘ah al-Shāṭibī: Worship During the Covid-19 Outbreak: Analysis of the Fatwa of the Indonesia Ulama Council Number 14 of Year 2020 Based on the Theory of Maqāṣid al-Sharī‘ah al-Shāṭibī - Kurniawan, Edi; Alhusni; Bin Syed Zaiful Hamzah, Syed Arif Asyraf (Jurnal Fiqh, 2022)
The Indonesian Ulama Council (MUI) has issued fatwa number 14 of the year 2020 on the Maintenance of Prayer in the Situation of the COVID-19 Outbreak. Issues that were fatwaed such as not holding Friday prayers and replacing with noon prayers, not congregating in mosques, the ban on holding religious activities in public areas with high COVID-19 contagion and so on. Therefore, this article will analyze the fatwa based on the theory of maqāṣid al-sharī‘ah al-Shāṭibī. Using the literature review method, this article concludes that the MUI fatwa has resulted in a response to the COVID-19 pandemic declaration that spread to Indonesia as well as provide guidance to the community regarding permission to worship in the COVID-19 epidemic situation. Studies show that the members of the MUI Fatwa Commission take into account the aspect of maslahah in the determination of fatwas. The maslahah refers to the theory of maqāṣid al-sharī‘ah al-Shāṭibī, and covers all levels whether the levels of ḍarūriyyah, ḥājiyyah and taḥsīniyyah.